Kidney Injury Molecule-1 and Cardiovascular Diseases: From Basic Science to Clinical Practice. (30th November 2015) - Medić, Branislava; Rovčanin, Branislav; Basta Jovanović, Gordana; Radojević-Škodrić, Sanja; Prostran, Milica
Abstract : Despite the recent findings concerning pathogenesis and novel therapeutic strategies, cardiovascular disease (CVD) still stays the leading cause of morbidity and mortality in patients with renal dysfunction, especially acute kidney injury (AKI). Early detection of patients with impaired renal function with cardiovascular risk may help ensure more aggressive treatment and improve clinical outcome. Kidney injury molecule-1 (KIM-1) is a new, promising marker of kidney damage which is currently the focus of countless studies worldwide. Some recent animal and human studies established KIM-1 as an important marker of acute tubular necrosis (ATN) and reliable predictor of development and prognosis of AKI. Food and Drug Administration (FDA) in USA acclaimed KIM-1 as an AKI biomarker for preclinical drug development. Recent data suggest the importance of monitoring of KIM-1 for early diagnosis and clinical course not only in patients with various forms of AKI and other renal diseases but also in patients with cardiorenal syndrome, heart failure, cardiopulmonary bypass, cardiothoracic surgical interventions in the pediatric emergency setting, and so forth. The aim of this review article is to summarize the literature data concerning KIM-1 as a potential novel marker in the early diagnosis and prediction of clinical outcome of certain cardiovascular diseases.